Current status and influencing factors of nurses’ work engagement in Chinese tertiary hospitals: A latent profile analysis - Xiaoli Zhong; Xian Rong; Yuxin Li; Wei Qing; Guiqiong Xie; Ping Dai; Jijun Wu; Lin He (PLoS ONE, 2025)
Background Work engagement is a work-related state of mind full of positivity and vigor. Understanding the current status and influencing factors of nurses’ work engagement is essential for improving the quality of nursing services and stabilizing the nursing workforce building. This study aimed to explore the potential categories of nurses’ work engagement and their influencing factors and provide a reference basis for developing targeted interventions to improve their work engagement. Methods From March to April 2024, 1,919 nurses from 12 tertiary hospitals in Sichuan Province, China, were enrolled in the study using convenience sampling. A demographic profile questionnaire, work engagement scale, and professional mission scale were used to investigate them. Latent profile analysis was used to explore the categories of nurses’ work engagement, and unordered multicategorical logistic regression was used to analyze the influencing factors of each category. Results Nurses’ work engagement could be categorized into three potential profiles: low work engagement group (n = 659, 34.3%), medium work engagement group (n = 763, 39.8%), and high work engagement group (n = 497, 25.9%). The unordered multi-categorical logistic regression results showed that marital status, reasons for choosing a nursing specialty, self-rated sleep quality, current work intensity, and sense of professional mission were influential factors affecting the potential profile of work engagement among nurses in tertiary care hospitals. Among them, unmarried nurses were more likely to belong to the low work engagement group; those who chose nursing specialties based on personal interest were more likely to belong to the medium work engagement group; those with medium work intensity were more likely to belong to the high work engagement group; and those with good self-assessed sleep quality and higher scores of sense of professional mission were more likely to belong to the medium and high work engagement groups. Conclusion The potential profiles of nurses’ work engagement in Chinese tertiary hospitals were dominated by the medium and low work engagement groups, with significant heterogeneity. Nursing managers should tailor interventions to enhance nurses’ sense of professional mission according to the characteristics of each type of nurse work engagement, thereby improving work engagement and nursing service quality.